2016
DOI: 10.1007/s12193-016-0231-x
|View full text |Cite
|
Sign up to set email alerts
|

VR-based operating modes and metaphors for collaborative ergonomic design of industrial workstations

Abstract: The aim of this paper is to evaluate two new operating design modes and their collaborative metaphors enabling two actors, a design engineer and an end-user, to work jointly in a collaborative virtual environment for workstation design. The two operating design modes that correspond to two different design paradigms include : direct design mode (the design engineer manipulates objects while the end-user specifies their activity constraints) and supervised design mode (the end-user manipulates objects while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Thus, its activity is monitored and analyzed by external actors [1] such as an ergonomist. In cases involving particularly low level of force exertion, the interaction can be ensured thanks to a 3D-joystick [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its activity is monitored and analyzed by external actors [1] such as an ergonomist. In cases involving particularly low level of force exertion, the interaction can be ensured thanks to a 3D-joystick [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Methods/Measurements [5,6,30,35,37,38,40,42] Rapid Upper Limb Assessment (RULA) [5,37,40] Rapid Entire Body Assessment (REBA) [1,30,36] Ergonomic Assessment Worksheet (EAWS) [35] National Institute for Occupational Safety and Health (NIOSH) [16] Ovako Working Posture Analysis System (OWAS) [1] Methods-Time Measurement (MTM-UAS) [14,41] Other (NASA-TLX questionnaire, Kinetic Energy ratio)…”
Section: Refmentioning
confidence: 99%
“…Different studies have showed that VR can be used as a tool in the design of workstations and for training purposes [2]. More specifically, it can be used in the ergonomic design of workstations, where a virtual environment can be easily tested and modified than a physical prototype [3,4].…”
Section: Vr Applied To Worktation Designmentioning
confidence: 99%